THE GUNUNGAN METAPHOR IN THE URIP IKU URUP VIDEO ART - adi, sigit purnomo; Mohamed Saat, Mohammad Khizal; Ajimahendra, Widy Dwi; Tri Marutama, I Gusti Ngurah (Capture : Jurnal Seni Media Rekam, 2021)
Urip Iku Urup is a highly printed artwork made from plastic waste that serves as video art. Environmentally friendly relief prints used as video artworks motivate studies on their meanings. Thus, this study's problem is how to visualize the metaphor of the mountains (Gunungan) in the Urip Iku Urup video art. This qualitative-descriptive study seeks to discover the Gunungan metaphor in the video art by using the metaphor approach. The findings demonstrate that Urip Iku Urup's work uses the Gunungan metaphor as a manifesto for the three relationships between God, man, and nature. Gunungan, as a teaching in Javanese life philosophy, implies human desire or hope for future accomplishments.